Perbaikan Diri Menurut Mohammad Iqbal (Telaah Teori Filsafat Islam) - Zulkarnain Zulkarnain (UIN Sumatera Utara, 2022)
Indonesia's political chaos starting from corruption, collusion, and nepotism is an unresolved problem and there is no clear point until now. There is no proper formula and solution to solve this problem. Like a building, Indonesia is a strong country but very easily collapsed due to political problems, starting from individuals and groups. Therefore it is necessary to have a strong and sturdy construction to support the building so that it does not collapse easily. The reconstruction that was built by M.Iqbal with khudi gave birth to a healthy and dynamic politics. As for things that can strengthen khudi: Love, Faqr, courage or enthusiasm, tolerance, lawful business, and honest and creative work. This can be used as a reconstruction in contemporary Indonesian politics. A sense of love and full responsibility will color individuals who are involved in politics. Khudi as a philosophical thought serves to strengthen the foundation of Indonesian politics which is easily shaken. The type of research used in this research is descriptive analysis research in which in this case the political reconstruction will be based on M.Iqbal's theory, namely khudi. library research method. As a recommendation to address solutions to various contemporary Indonesian political problems, the political reconstruction offered by M.Iqbal with his khudi is considered necessary and able to answer these political problems.